Inductive role of the brown alga Sargassum polycystum on growth and biosynthesis of imperative metabolites and antioxidants of two crop plants - Mohammed, Soha; El-Sheekh, Mostafa M.; Hamed Aly, Saadia; Al-Harbi, Maha; Elkelish, Amr; Nagah, Aziza (Frontiers in Plant Science, 2023)
The potential of macroalgae as biostimulants in agriculture is proved worthy. Vicia faba and Helianthus annuus are socioeconomic crops owing to their increasing demand worldwide. In this work, we investigated the energetic role of seed presoaking and irrigation by the brown seaweed, Sargassum polycystum aqueous extract (SAE) on certain germination and growth traits, photosynthetic pigments, carbohydrates, phenolics, flavonoids, and the total antioxidant activity. In comparison to the control plants, our consequences revealed that seeds that received the SAE improved all the germination and growth criteria except for both crop plants. Furthermore, the SAE significantly increased the carotenoids, total photosynthetic pigments, and total carbohydrates by (14%, 7% and 41%) for V. faba and (and 17%, 17%, and 38%) for H. annuus, respectively. Phenolics and flavonoids were significantly induced in Vicia but slightly promoted in Helianthu plants, whereas the total antioxidant activity in both crops non significantly elevated. Even though The NPK contents were significantly stimulated by the SAE in Vicia plants, the effect was different in Helianthus, where only nitrogen content was significantly enhanced, whereas phosphorus and potassium showed little enhancement. Thus, the SAE treatment to be one of the superlative sustainable strategies for food, feed and as soil health.